Mendelian randomization of serum micronutrients and osteoarthritis risk: focus on zinc - Wenxing Zeng; Enda Hong; Wei Ye; Luyao Ma; Dejun Cun; Feng Huang; Ziwei Jiang (Nutrition Journal)
Abstract Background Osteoarthritis (OA) is an increasingly severe public health issue globally. Micronutrients are essential for maintaining normal physiological functions and metabolic balance; however, their relationship with OA is not fully understood. Methods This study aimed to evaluate the potential causal relationships between 15 key micronutrients and the risk of OA using both two-sample and multivariate Mendelian randomization approaches. We gathered data from a large prospective cohort of genome-wide association studies on these micronutrients and OA. Comprehensive Mendelian randomization analyses were conducted using inverse variance weighting, MR Egger, weighted median, weighted models, and simple models. Through multivariate analyses, factors such as BMI and strenuous exercise were controlled to assess the independent associations between zinc and OA risk. Results In the two-sample Mendelian randomization analysis, zinc was positively associated with OA risk (OR = 1.045, 95% CI: 1.009 to 1.082, P = 0.015). This association remained significant even after controlling for other confounding factors in multivariate analyses, indicating an independent effect of zinc. Other micronutrients, such as calcium, iron, and vitamin D, did not show significant associations with OA risk in this study. Conclusion This study provides new evidence of a positive association between the micronutrient zinc and the risk of OA, emphasizing the importance of considering micronutrients in osteoarthritis prevention and treatment strategies. Future research should further validate these findings and explore the specific biological mechanisms by which zinc influences the risk of osteoarthritis.